Peran Guru dalam Mengatasi Kesulitan Belajar Siswa pada Materi Pewarisan Sifat di MTs Darul Ulum Budi Agung Medan - Azura, Dedek; Nainggolan, Tsaabitah Husnaa Br; Ulfa, Syarifah Widya (YASIN, 2024)
This study aims to identify students' learning difficulties in understanding the material of inheritance of traits at MTS Darul Ulum Budi Agung Medan. The ease of learning experienced by students can be caused by various factors, including individual cognitive abilities and teaching methods applied by teachers. This study used a qualitative approach with a population of 36 grade 9 students. Data were collected through interviews, observations, and questionnaires that measured the level of learning difficulties. The pretest results showed that the average student score was in the range of 20-40, while the posttest showed an increase to 60-70, although still below the Minimum Completion Criteria (KKM). These findings indicate that students have difficulty in understanding basic genetic concepts, such as genes and Mendel's laws of inheritance, which are exacerbated by low student motivation and interest and less interactive teaching methods. This study concludes that to improve student understanding, teachers need to apply more varied and interesting learning methods and provide additional support for students who experience difficulties.